RANCANG BANGUN SISTEM PENDAFTARAN DAN BRACKET OTOMATIS PADA TURNAMEN ESPORT BERBASIS WEB - Ahmad Marsehan; Rizka Aulia; Shinta Aprilisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The organization of esport tournaments at various levels, ranging from communities to educational institutions, continues to grow rapidly. However, the process of participant registration and match bracket management that is still carried out manually has the potential to cause data recording errors, irregular scheduling, and low efficiency in tournament management. This study aims to design and build an automatic registration and bracket system for web-based esport tournaments. The methods used include needs analysis, system design, implementation, and testing. The system was developed on a web-based platform to allow online access by both committee members and participants. The main features include online team registration, participant data management, automatic bracket generation based on the number of registered teams, as well as real-time presentation of match schedules and results. The results of the study indicate that this system is capable of managing registration and bracket arrangement more effectively and efficiently. In conclusion, this system has succeeded in becoming a digitalization solution for tournament management, with key benefits including minimizing data errors, improving the regularity of match scheduling, and facilitating easier access to information for all parties involved. The automation of this web-based system represents a strategic step in supporting the continuously growing esport ecosystem.